IMPLEMENTASI EDUKASI POLA HIDUP BERSIH DAN SEHAT DAN NUTRISI MELALUI PROGRAM “PETUALANGAN SEHAT SI HEBAT” PADA SISWA SD NEGERI 12 SUNGAI SAPIH - Erdanela Setiawati; Jelmila, Sri Nani; Hawa Arma Putri; Mardonal, Mardonal; Pela Masri; R. Dhea Pratiwi Novrianti; Tiara Tri Ananda Putri; Rada Tri Utami; Nadillah Karunia Ilahi (Yayasan Nusantara Hasana Berdikari, 2026)
Early health education on clean and healthy living behavior (PHBS) and nutrition plays an important role in establishing healthy lifestyle habits among school-aged children. However, many students still have limited understanding of PHBS practices and healthy food choices, highlighting the need for effective health education interventions. This community service activity aimed to improve students’ knowledge of PHBS and nutrition through an educational and interactive approach. The activity was conducted on December 13, 2025, at SD Negeri 12 Sungai Sapih and involved 135 students from various grade levels. The program was delivered through the “Petualangan Sehat Si Hebat” concept using visual media and participatory educational activities. The topics included proper handwashing, personal and environmental hygiene, cough and sneeze etiquette, and healthy food selection. Evaluation was carried out using pre-test and post-test questionnaires. The results indicated an increase in students’ knowledge and high enthusiasm during the activity. Creative and interactive health education proved effective in improving students’ understanding of PHBS and nutrition from an early age.